Redes de distribuição de água e a transformação digital: identificação de tendências e lacunas com apoio em análise bibliométrica - Ferreira, Ligia Lulai (Universidade Federal de São Carlos, 2022)
Due to the dynamic nature of water distribution systems, their operational management ideally should be supported by hydraulic modeling, which is recommended by ABNT NBR 12.218/2017 as a planning and operation instrument. Hydraulic models are tools capable of representing in simulations the behavior of the system, according to its physical, logical and topological configuration, making it possible to analyze its current conditions and make predictions. In order to achieve the purpose of operational management supported by modeling, instead of only using it as punctual applications for specific analysis, the quality of the asset register, real-time monitoring capabilities, data analysis, forecasting and anomaly detection models are increasingly relevant. Given NBR 12.218; Decree No. 9.9.83, of 2019, which sets as a goal the implementation of Building Information Modeling (BIM) for engineering works and services; and Decree No. 10.306 which determines BIM be applied to building’s operations and management as far year 2028, the objective of this research was to investigate the relationships between these tools in the context of the water sector’s digital transformation focusing on water distribution networks. Therefore, a literature bibliometric review was conducted based on three research axes, comprising 114 articles: 1) Hydraulic modeling and operational management; 2) Information models and distribution networks; 3) Smart water and related concepts. Among the main results, it was observed that until 2015, the research focus mostly lied on subjects related to hydraulic modeling and calibration methods. From 2016, topics related to more dynamic approaches, such as real-time monitoring, cyber security and smart water started gaining traction, with great interest in smart metering and the use of IoT technologies. There was a prevalence of studies focusing on technical solutions addressing benchmark systems, considering systems already calibrated and with well-known hydraulic parameters, and a gap was found in research relating to the practical needs of service providers, such as business cases evidencing the advantages and opportunities of return on investments in digital technologies.
Water distribution networks and digital transformation: identification of trends and gaps supported by bibliometric analysis
Keywords: Modelagem hidráulica; Água inteligente; Modelo de informação; BIM; Hydraulic modelling; Smart water; Information model; Building information modeling; ENGENHARIAS::ENGENHARIA CIVIL::ENGENHARIA HIDRAULICA; ENGENHARIAS::ENGENHARIA SANITARIA; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::INSTALACOES HIDRAULICO-SANITARIAS; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::TECNICAS DE ABASTECIMENTO DA AGUA